The LifeShirt: a multi-function ambulatory system monitoring health, disease, and medical intervention in the real world - Grossman, Paul (Studies in health technology and informatics, 2004)
Despite advances made in health-related ambulatory monitoring, medical practitioners and researchers have remained seriously constrained in their ability to acquire concurrent assessments of multiple physiological systems, as well as patient reports of symptoms and well being in daily life: Almost all past and current applications have been limited to the registration of a single variable (e.g. the electrocardiogram or blood pressure), and this has resulted in incomplete information about other relevant physiological and environmental factors likely to contribute to disease or its amelioration. Monitoring of multiple physiological functions has been too complicated to achieve and has required special measurement devices that have been unavailable, too expensive, or too cumbersome to effectively employ. Concurrent assessment of pertinent information about patient activities during monitoring has remained difficult to accomplish, although such information is likely to be crucial for the interpretation of physiological findings and patients' perceptions of improvement. The LifeShirt (Vivometrics, Inc., Ventura, CA, U.S.A.) is a multi-function ambulatory device capable of simultaneously monitoring several physiological signals and patient reports of symptoms and well being. The LifeShirt system is an extensible data acquisition and processing platform consisting of a garment, a data recorder, and PC-based analysis software. Sensors in the LifeShirt garment continuously monitor respiration, the electrocardiogram, activity and posture. Other functions are easily plugged into the system, including pulse oximetry, EEG/ EOG measurement, blood pressure, temperature, capnometry and acoustic monitoring. Subjective patient data may also be entered into the LifeShirt recorder, and all data are encrypted and written to a flash memory card. Vivologic(TM) analysis software provides full-disclosure analysis and display of high-resolution waveforms and over 30 derived parameters; the software also produces summary reports for clinical diagnostic purposes. The LifeShirt has been rigorously tested for more than 38,000 hours in 90 studies with 1,750 subjects. The device has received all necessary regulatory approvals and is currently used in leading research institutions throughout the United States, Canada and Europe. Clinical applications include sleep diagnostics, heart disease, pulmonary disorders, cardiopulmonary rehabilitation, early hospital discharge and pre- and post-operative monitoring, human-factors in ergonomics and behavioral medicine.